Wrecked : an IQ novel - Ide, Joe (Ide, Joe. IQ novel., 2018)
Isaiah Quintabe--IQ for short--has never been more successful, or felt more alone. A series of high-profile wins in his hometown of East Long Beach have made him so notorious that he can hardly go to the corner store without being recognized. Dodson, once his sidekick, is now his full-fledged partner, hell-bent on giving IQ's PI business some real legitimacy: a Facebook page, and IQ's promise to stop accepting Christmas sweaters and carpet cleanings in exchange for PI services. So when a young painter approaches IQ for help tracking down her missing mother, it's not just the case Isaiah's looking for, but the human connection. And when his new confidant turns out to be connected to a dangerous paramilitary operation, IQ falls victim to a threat even a genius can't see coming. Waiting for Isaiah around every corner is Seb, the Oxford-educated African gangster who was responsible for the death of his brother, Marcus. Only, this time, Isaiah's not alone. Joined by a new love interest and his familiar band of accomplices, IQ is back--and the adventures are better than ever.